2019
DOI: 10.1111/jon.12658
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Integration of Automated Processing for Brain Quantitative Susceptibility Mapping: Multi‐Site Reproducibility and Single‐Site Robustness

Abstract: Quantitative susceptibility mapping (QSM) of the brain has become highly reproducible and has applications in an expanding array of diseases. To translate QSM from bench to bedside, it is important to automate its reconstruction immediately after data acquisition. In this work, a server system that automatically reconstructs QSM and exchange images with the scanner using the DICOM standard is demonstrated using a multi-site, multi-vendor reproducibility study and a large, single-site, multi-scanner image quali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 51 publications
(68 reference statements)
1
27
0
Order By: Relevance
“…Previous studies at 1.5T and 3T have shown good reproducibility for χ and R 2 * data acquired on the same scanner or across sites (1.5T and 3T) ( Hinoda et al., 2015 ; Cobzas et al., 2015 ; Deh et al., 2015 ; Lin et al., 2015 ; Santin et al., 2017 ; Feng et al., 2018 ; Spincemaille et al., 2019 ). In terms of QSM and depending on the subcortical region, intra-scanner 3T repeatability studies report an SD w of 0.002–0.005 ppm ( Feng et al., 2018 ) and 0.004–0.006 ppm ( Santin et al., 2017 ), and the cross-site 3T study by Lin et al.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Previous studies at 1.5T and 3T have shown good reproducibility for χ and R 2 * data acquired on the same scanner or across sites (1.5T and 3T) ( Hinoda et al., 2015 ; Cobzas et al., 2015 ; Deh et al., 2015 ; Lin et al., 2015 ; Santin et al., 2017 ; Feng et al., 2018 ; Spincemaille et al., 2019 ). In terms of QSM and depending on the subcortical region, intra-scanner 3T repeatability studies report an SD w of 0.002–0.005 ppm ( Feng et al., 2018 ) and 0.004–0.006 ppm ( Santin et al., 2017 ), and the cross-site 3T study by Lin et al.…”
Section: Discussionmentioning
confidence: 83%
“…R 2 * imaging and QSM have been shown to provide reproducible results in single-site and cross-site studies at 1.5T and 3T ( Hinoda et al., 2015 ; Cobzas et al., 2015 ; Deh et al., 2015 ; Lin et al., 2015 ; Santin et al., 2017 ; Feng et al., 2018 ; Spincemaille et al., 2019 ).…”
Section: Introductionmentioning
confidence: 96%
“…This CAT QSM + qBOLD OEF mapping eliminates assumptions in and, therefore, is theoretically more accurate than other OEF mapping methods ( Kudo et al, 2016 ; Uwano et al, 2017 ; Zhang et al, 2017 , 2018 ). QSM ( de Rochefort et al, 2010 ; Wang and Liu, 2015 ; Liu et al, 2018 ) has been shown to be highly reproducible ( Deh et al, 2015 ; Spincemaille et al, 2019 ), and recent technical developments in preconditioning for optimization execution ( Liu et al, 2016 ) and in phase unwrapping ( Dong et al, 2015 ) promise to make QSM robust even in brain regions near the air–tissue interface. The challenge of qBOLD prone to noise is effectively addressed by the CAT algorithm.…”
Section: Discussionmentioning
confidence: 99%
“…31 Finally, morphologyenabled dipole inversion with automatic uniform cerebrospinal fluid (CSF) 0 reference (MEDI+0) algorithm was used to compute susceptibility. [32][33][34][35][36][37] The mGRE magnitude was modeled according to qBOLD and further denoised according to the cluster analysis of time evolution (CAT) by following the approach outlined by Cho et al 27 with incorporating tissue type information by tripling the number of clusters into gray matter (GM), white matter (WM), cerebrospinal fluid clusters, and without the OEF regularization in the QQ-CAT optimization. The cluster-specific v values are initialized to be 4/2/0% for GM/ WM/cerebrospinal fluid clusters.…”
Section: Qq Oef and Cmro 2 Mapping From Gre Data At Baseline And Atmentioning
confidence: 99%